The Study of Procurement in the Past Decade of Maluan Subdistrict Administrative Organisation, Phunphin, Suratthani - สุทธิ์ประเสริฐ สุภาพร (Thai Interdisciplinary and Sustainability Review, 2019)
The purposes of this study were to analyse procurement process including comparative analysis of procurement in the division of land and buildings in the past 10 years (B.E. 2545-2554) of Maluan Subdistrict Administrative Organisation, Phunphin, Suratthani, by analysing data from documents and primary sources which were performance reports according to the procurement plan, statement of financial position for the fiscal years of B.E.2545-2554 and the budget provision of B.E.2545-2554 by using comparative analysis on the tables of the material procurement processes under the land and building section including typology analysis on each year. The results showed that over the past ten years Maluan Sub-district Administrative Organisation set a budget for land and buildings of Maluan Sub-district Administrative Organisation from three sources in the total of 87,136,553.00 baht, which comprised of yearly expense 47,720,178 baht, reserves 32,557,875 baht, and special subsidies 6,858,500 baht that was mostly paid for the street projects. As for setting ten-year procurement processes for 252 projects of land and buildings, there were projects that followed the annual purchase plan and procurement processes of 206 projects and 46 projects that did not follow material procurement processes. Of the total budget 87,136,553.00 baht, 70,078,566.18 Baht was paid according to the plan but 17,057,986.82 baht was not timely paid at the right time. This could be concluded that the operation of Maluan Sub-district Administrative Organisation was still inefficient and ineffective.